Leadership, Organizational Culture, and Work Environment: Drivers Of Employee Discipline - Putri, Diny Ayu Ermalia; Adhimursandi, Doddy; Sampeliling, Alexander (Economics and Business Solutions Journal, 2024)
Leadership style, organizational culture, and work environment are crucial factors influencing employees' work discipline. This study investigates these factors' impact on employees' work discipline in the Secretariat Section of the Public Works Department, Kutai Kartanegara Regency, Indonesia. The research employed a quantitative approach with a sample of 75 respondents using the census method for sampling. Data analysis was performed using SEM with SmartPLS Version 4. The findings indicate that leadership style has a positive, although statistically negligible, impact on work discipline. On the other hand, both organizational culture and work environment have positive and statistically significant impacts on work discipline. This study emphasizes proficient leadership, robust corporate culture, and a conducive work environment to foster employee discipline. The findings suggest that organizations should develop participatory and employee-oriented leadership styles, foster a culture of innovation and teamwork, and provide a conducive physical and non-physical work environment to enhance employee discipline and overall organizational performance. This study enhances the comprehension of the variables influencing work discipline in public sector organizations. It provides practical implications for managers and policymakers in designing strategies to improve employee discipline and organizational effectiveness